(untitled) (Fiep Bulletin - online, 2011)
The term amputation has the meaning of the partial or total withdrawal of one or more limbs. This research was developed at the Rehabilitation Center of Assis Gurgacz College-FAG, where 20 individuals with transfemoral amputation were interviewed, aged between 19-84 years, who were conducting monitoring or rehabilitation. This is a field study, epidemiological, quantitative cross-sectional. Its main objective was to identify the major complications during the pre-fitting. As instrument, it was used a questionnaire with 23 questions, applied between the months of April to June 2009, where we were able to identify the major complications found after amputation. After collecting the data, it was found that phantom pain was one of the most common among the major complications, and more than half of the questioned people reported the change, and related to the type of scarring resulting from the surgical process. All respondents who had phantom pain were welcomed with amputation, therefore the presence of phantom pain in the sample studied, has no correlation with the acceptance because this is an emotional factor. It was also observed that the banding was not a factor that showed a direct relation with the phantom pain.